Islamic principles in graphic design / Azahar Harun...[et al.] - Harun, Azahar; Abd Razak, Mohamed Razeef; Mohamad, Fadly; Mohd Radzuan, Lili Eliana (Universiti Teknologi MARA Cawangan Pahang, 2014)
This paper discusses the advantage of Islamic Principles namely Tawheed, Iqtisad, Haya and Dhikir in regard to graphic design. From the results of the visual analysis conducted on selected samples (symbols and logos), it is found that the visual communication aspect of graphic design does not only comply with Gestalt Principles but could also be linked to Islamic Principles. In this sense, we conclude that the application of Islamic principles is relevant thus should be adopted as a standard design vocabulary in the teaching and learning of graphic design in Universiti Teknologi MARA (UiTM).